2004
DOI: 10.1111/j.1745-493x.2004.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in Buyer‐Seller Relationships: Does Gender Matter in Purchasing?

Abstract: SUMMARY While differences between male and female salespeople are well documented in the literature, evidence is less clear whether these differences matter to the buyer or whether buyers of different gender make decisions differently. The article reports results of a survey of male and female purchasers on the behaviors, trust, credibility and customer orientation of a salesperson. Almost no differences were found on any of the variables for male or female buyers. This calls into question past research that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…It is noted that the Successful salesperson was coded as 1 and the Unsuccessful salesperson was coded as 2 in the data file and that relational behavior is reverse coded. The findings for the three trust components are similar to the propositions from the Walker, Churchill, and Ford 1979 proposition that trust is an antecedent to other successful sales behaviors, and replicates similar findings for higher trust factor ratings by buyers for successful salespersons by Plank, Reid, and Pullins (1999) and Pullins, Reid, and Plank (2004). This finding also lends credence to a 20 year old study in which a successful sale was the outcome of trust by the buyer in the salesperson (Anderson and Narus 1984).…”
Section: Discussion Of Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…It is noted that the Successful salesperson was coded as 1 and the Unsuccessful salesperson was coded as 2 in the data file and that relational behavior is reverse coded. The findings for the three trust components are similar to the propositions from the Walker, Churchill, and Ford 1979 proposition that trust is an antecedent to other successful sales behaviors, and replicates similar findings for higher trust factor ratings by buyers for successful salespersons by Plank, Reid, and Pullins (1999) and Pullins, Reid, and Plank (2004). This finding also lends credence to a 20 year old study in which a successful sale was the outcome of trust by the buyer in the salesperson (Anderson and Narus 1984).…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…Walker, Churchill, and Ford (1979) proposed trust as an antecedent to other successful sales behaviors. Although Plank, Reid, and Pullins (1999) and later Pullins, Reid, and Plank (2004) found that successful sales persons were rated higher for trust factors by buyers than were unsuccessful sales persons, and a clearly positive outcome of trust is a successful sale (Anderson and Narus 1984), most other studies found that trust was unrelated to sales performance (Chow, Reed, and Holden 1997; Crosby, Evans, and Cowles 1990; Doney and Cannon 1997). Thus, following the propositions by Walker, Churchill, and Ford, and the findings from Plank, Reid, and Pullins, and later by Pullins, Reid, and Plank, the second hypothesis of this study holds that:…”
Section: Relational Sellingmentioning
confidence: 97%
“…In the SCM context, having women in the TMT has certain distinct advantages. As noted in the supply chain literature, firms employing women tend to generate perceptions of greater credibility and trustworthiness (Pullins, Reid & Plank, 2004). This is an important issue given the challenges in obtaining supplier commitment to align with the environmental agenda of a firm (Walker, Di Sisto & McBain, 2008).…”
Section: Female Representation In Tmtsmentioning
confidence: 99%
“…A dyadic approach to this issue viewing both female buyers and sellers would be particularly beneficial. Research has examined only the role of female sellers (Piercy, Cravens, and Lane 2001) or only female buyers (Pullins, Reid, and Plank 2004). Studying females that are involved in sales and in purchasing within the same context might shed additional light on this issue.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%